Visibilidade midiática, discurso e território: em busca de uma identidade para o desenvolvimento - Pippi, Joseline (2012)
The world-historical period allows communities to show their specific traits, showing them as brands in their distinct cultural self-assertion and legitimizing their identities - many of them territorialized. The stage for these desired evidence of such peculiarities is the media. This thesis aims to uncover the relationship between media visibility, territorial identity and devel-opment in the regions of the Quarta Colônia (RS-Brazil) and Aljarafe-Doñana (Seville, Spain). The area was operated due to the fact that in both regions, regular newsletters are pro-duced by associations of territorial development, that show the territorial identity as unique features. Interested to discover how identities are territorialized and also shown on media. The starting point of the study was the analysis of two magazines and one newspaper produced by the associations related to the development of rural regions, respectively: Magazines Adad and Tierra Sur and also Caderno Quarta Colônia. The second groups of newspapers analyzed were Diário de Santa Maria and Diario de Sevilla, in order to verify the integration of tradi-tional associations in the news space. To address the complexity of the problem, we devel-oped a Composite Analytical Matrix (CAM), formed by the Documental Analysis and Dis-course Analysis of the corpora. The study showed that local identity was used rationally as hand tools, mint visibility of the territories as part of a strategic action aimed to developing the rural areas, in addition, were observed that the media discourse has been touted as a tactic in legitimacy and recognition of the favorable discourse of development, published in the magazines and the newspaper produced by the associations.